2020
DOI: 10.1039/d0cc05699e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of heterocyclic compounds through nucleophilic phosphine catalysis

Abstract: Nucleophilic phosphine catalysis is a practical and powerful synthetic tool for the synthesis of various heterocyclic compounds with the advantages of environmental-friendly, metal-free, and mild reaction conditions. The present report...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 117 publications
(37 citation statements)
references
References 387 publications
0
37
0
Order By: Relevance
“…Heterocyclizations are powerful tools for the synthesis of five-membered heterocycles that are often found in natural products , and synthetic pharmaceuticals and widely used in material science and organic synthesis. Recent studies revealed that oxidative heterocyclizations could evoke novel and useful catalytic transformations, which otherwise are difficult to achieve. For example, the cyclization of ketene dithioacetals, a kind of electron-rich olefin, under electrochemical conditions afforded the cyclic amino acid derivatives (Scheme a, X = NH) .…”
mentioning
confidence: 99%
“…Heterocyclizations are powerful tools for the synthesis of five-membered heterocycles that are often found in natural products , and synthetic pharmaceuticals and widely used in material science and organic synthesis. Recent studies revealed that oxidative heterocyclizations could evoke novel and useful catalytic transformations, which otherwise are difficult to achieve. For example, the cyclization of ketene dithioacetals, a kind of electron-rich olefin, under electrochemical conditions afforded the cyclic amino acid derivatives (Scheme a, X = NH) .…”
mentioning
confidence: 99%
“…The compounds ( Fig. 1 ) 3-(4,5-dinitro-imidazol-1-yl)prop-2-yn-1-amine (1), 2-chloro-N-[3-(4,5-dinitro-imidazol-1-yl)prop-2-ynyl]acetamide (2), N-[3-(2-methyl-4,5-dinitro-imida-zol-1-yl)prop-2-ynyl]-3-phenyl-oxiran-2-amine (3), 1-[3-[(3-phenyloxiran-2-yl)amino] prop-1-ynyl]imidazole-4,5-diamine (4) and 3-[3-[(3-phenyloxiran-2-yl)amino]prop-1-ynyl]-4,6,7,9-tetrahydroimidazo[4,5-b] 1 4 diazocine-5,8-dione (5) were prepared using a previously reported method 11 . The other reagents were acquired from Sigma-Aldrich Co.…”
Section: Methodsmentioning
confidence: 99%
“…As far as their utilization in synthesis is concerned, it has been limited to very few examples. In the cases reported to date, [ 25 ] the dienophile counterparts were limited to dimethyl acetylenedicarboxylate and acetylenedicarboxylic acid. The conditions used for their synthesis have generally led, in modest yields, to mixtures of stereoisomers and regioisomers (pincer vs. domino).…”
Section: Introductionmentioning
confidence: 99%